Rancangan Eksperimen Sederhana proses destilasi Air garam Menjadi Air Tawar Untuk Pemahaman Kosep Penguapan Pada Siswa SMA - Fatimah Fatimah; Muhammad Subhan; Eka Rahmawati; Irawati Hi. Malan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Research has been conducted on the design of a water distiller to produce fresh water converted from seawater through a distillation process. This research aims to be a learning material for high school physics to understand the concept of evaporation. The method in this research is to carry out the process of heating, evaporation and condensation using an electric heater that has been modified as needed such as adding pipes and cooling tubes and conducting performance tests of the designed tool. The results of the research data obtained from the results of measuring the volume of distilled water and the quality of water produced. The data of distillation results include the volume of fresh water with an average of 93 with a standard deviation of 185 ph average of 7.4 with a standard deviation of 14.7, the number of particles contained with an average of 42 with a standard deviation of 83.4 and a temperature with an average of 103 with a standard deviation of 206 with the resulting water quality parameters including colourless water with fresh taste and odourless. Based on the quality tests that have been carried out, it can be concluded that the distilled water is suitable for consumption based on the drinking water quality standards